Unions in America - Chaison, Gary N.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2006)
'Unions in America' provides a concise and current introduction to what America's labour unions do and why they do it. Chaison portrays America's unions as complex, self-governing organisations that are struggling to regain their lost membership, bargaining power, and political influence.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Labor unions -- United States; Industrial relations -- United States; Electronic books